Discovery of biaryl carboxylamides as potent RORγ inverse agonists. Issue 15 (1st August 2015) - Chao, Jianhua; Enyedy, Istvan; Van Vloten, Kurt; Marcotte, Douglas; Guertin, Kevin; Hutchings, Richard; Powell, Noel; Jones, Howard; Bohnert, Tonika; Peng, Chi-Chi; Silvian, Laura; Hong, Victor Sukbong; et al.
Graphical abstract